Ultrasonographic, clinical, and pathological features of papillary thyroid carcinoma in children and adolescents with or without Hashimoto’s thyroiditis - Jie, Yue; Ruan, Jingliang; Luo, Man; Liu, Rongbin (Frontiers in Oncology, 2023)
Objective. To compare the ultrasonographic, clinical, and pathological features of children and adolescents with papillary thyroid carcinoma (PTC) with and without Hashimoto's thyroiditis (HT) Materials and Methods. A total of 52 children and adolescent patients surgically diagnosed with PTC between 2017 and 2022 were included; 14 children and adolescent patients with PTC were diagnosed with HT via pathological examination. The preoperative ultrasonographic, postoperative histological, and molecular and clinical characteristics were retrospectively analyzed.Results. The prevalence rate of PTC in patients with HT was 27%. Papillary thyroid microcarcinomas were found in 11 of 38 patients without HT, but none in patients with HT (p = 0.023). Extrathyroidal extension, capsular invasion, and lymph node metastases were more frequent in patients with PTC and HT than in patients with PTC alone (p < 0.05 for both). The ultrasonographic features of nodule composition, echogenicity, shape, margin, Thyroid Imaging Reporting and Data System categories, and total points were similar. The patterns of echogenic foci were more prominent in the nodules of patients with HT than in those of patients without HT (p = 0.016).Conclusion. The frequency of papillary thyroid microcarcinomas in patients with PTC and HT was less, whereas that of extrathyroidal extension, capsular invasion, and lymph node metastasis was significantly higher in patients with PTC and HT than in those with PTC alone. The patterns of echogenic foci on ultrasonography may represent a risk for PTC.